2017
DOI: 10.21303/2461-4262.2017.00364
|View full text |Cite
|
Sign up to set email alerts
|

Classifying the Ice Seasons 1982-2016 Using the Weighted Ice Days Number as a New Winter Severity Characteristic

Abstract: Sea ice is a key climate factor and it restricts considerably the winter navigation in severe seasons on the Baltic Sea. So determining ice conditions severity and describing ice cover behavior at severe seasons are necessary. The ice seasons severity degree is studied at the years 1982 to 2016. A new integrative characteristic named the weighted ice days number of the season is introduced to determine the ice season severity. The ice concentration data on the Baltic Sea published in the European Copernicus P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…Trichinella spiralis could be infecting wildlife in Estonia similarly as described by Oksanen and others [ 22 ], as spillover from the domestic cycle. That we did not find freeze-sensitive T. spiralis in the main reservoir animal host species in our previous study [ 6 ] might be explained by two consecutive colder years before 2011/2012 [ 26 ].…”
Section: Discussionmentioning
confidence: 77%
“…Trichinella spiralis could be infecting wildlife in Estonia similarly as described by Oksanen and others [ 22 ], as spillover from the domestic cycle. That we did not find freeze-sensitive T. spiralis in the main reservoir animal host species in our previous study [ 6 ] might be explained by two consecutive colder years before 2011/2012 [ 26 ].…”
Section: Discussionmentioning
confidence: 77%
“…A similar result was found by Klais et al [20] which indicated that the local physical conditions (mild and variable winters) resulting from large-scale changes in weather patterns may be more crucial factors than nutrients in explaining the shift towards dinoflagellate dominance. Changeable weather in winter and spring: Since the 1990s, stratification collapse (strong mixing events) has frequently occurred in winters from October to April when saline and thermal stratification decreases [45]. Winters have become increasingly inconstant, with extremely high air temperatures for short periods [46]. High air temperatures cause sea ice melting and reduce its thickness.…”
Section: Discussionmentioning
confidence: 99%
“…Changeable weather in winter and spring: Since the 1990s, stratification collapse (strong mixing events) has frequently occurred in winters from October to April when saline and thermal stratification decreases [45]. Winters have become increasingly inconstant, with extremely high air temperatures for short periods [46]. High air temperatures cause sea ice melting and reduce its thickness.…”
Section: Discussionmentioning
confidence: 99%
“…2). Negative values of Δch indicated the seasons (winters) in which ice cover lasted longer, whereas positive values indicated the seasons (winters) in which the ice cover was extensive for some time but did not last long [20]. Therefore, the difference Δch of the season shifted from the negative to positive.…”
Section: Regime Shift In the Baltic Sea / Promjena Režima Na Baltičkomentioning
confidence: 99%
“…The winters in the initial parts had relatively long-lasting ice cover. At the end of the studied period, maximal ice cover stayed only for a short time [17].…”
Section: Introduction / Uvodmentioning
confidence: 96%